THE RELATIONSHIP BETWEEN FOOD SECURITY AND WASTING INCIDENTS IN TODDLERS - Anis, Nur Anis Safitri; Harianti, Rini; Fikri, Al Mukhlas (HEARTY, 2025)
Wasting is still a major nutritional problem in Indonesia with a prevalence of 8.5%, exceeding the WHO threshold of 5%. Household food security plays an important role in preventing wasting, especially in areas with high economic vulnerability such as Cipicung and Sukatani Villages. This study aims to analyze the relationship between household food security and the incidence of wasting in toddlers. This study was an observational analytical study with a cross-sectional design involving 110 toddlers aged 6–59 months. Data were collected through anthropometric measurements and the Food Insecurity Experience Scale (FIES) questionnaire. The results showed that 93.6% of families were in the category of severe food security, and as many as 13.6% of toddlers experienced wasting. Bivariate analysis using gamma correlation test showed a significant relationship between food security and wasting with a value of p = 0.014. Poor food security increases the risk of wasting due to limited access to nutritious food. The conclusion of this study is that household food security has a significant relationship with the incidence of wasting in toddlers, so there is a need for interventions that focus on improving food security at the community level.